Implementasi Metode Rational Unified Process dalam Rancang Bangun Sistem Kepegawaian Berbasis Web PT ABC - Julianti, Revicha Sri Aren; Farisi, Ahmad; Dafid (Journal of Informatics and Advanced Computing (JIAC), 2024)
The employee information system is a collection of interconnected subsystems related to employee data within a company, aimed at providing information on planning, organizing, operations, and decision-making. With technological advancements, this system is designed to manage the collection, processing, storage, and reporting of employee data and can be implemented in various organizations. This research designs a web-based employee information system for PT ABC, a logistics company with 25 employees that currently manages its workforce manually. The system handles recruitment, attendance, leave, and resignation processes, improving data integrity and facilitating management. With differentiated access rights for administrators, directors, and employees, as well as specific features for prospective employees, the system is expected to enhance the company’s operational efficiency.